A Fe2O3, Ag2O and La 0.67 Ca 0.33 MnO3 three-phase co-composite ceramic and a preparation method thereof
Three-phase co-composite ceramics were prepared by multiphase composite of Fe2O3, Ag2O and La0.67Ca0.33MnO3, which solved the problem of low magnetoresistance (MR) of single-phase polycrystalline manganese ore ceramics and achieved a significant improvement in magnetoresistance performance and expanded application.
Patent Information
- Application Number
- CN202510635543.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-05-16
AI Technical Summary
The intrinsic magnetoresistance (MR) of single-phase polycrystalline manganese ore ceramic materials is low, which limits their practical application in fields such as magnetoresistive sensors. The optimization effect of existing two-phase composite materials on magnetoresistive performance is limited.
Three-phase co-composite ceramics were prepared by multiphase composite of Fe2O3, Ag2O and La0.67Ca0.33MnO3. The grain boundary coating of Fe2O3 and the grain connectivity of Ag2O were utilized to enhance the continuous mobility of charge carriers and the ordering of electron spin, thereby improving the upper limit of the MR value of the material.
It effectively improves the magnetoresistive performance of three-phase composite ceramics by 25% compared to single-phase materials, while maintaining other performance advantages and without producing negative effects, thus expanding the application prospects of composite ceramics in related fields.
Smart Images

Figure CN120518394B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of novel functional composite ceramic magnetic storage technology, and relates to a Fe2O3, Ag2O and La... 0.67 Ca 0.33 MnO3 three-phase co-composite ceramics and their preparation methods. Background Technology
[0002] Polycrystalline manganese ore ceramics La 0.67 Ca 0.33 MnO3 (LCMO) materials exhibit great application potential in magnetic sensors, magnetic storage, and spintronic devices due to their unique multiphase strong coupling of charge, lattice, orbitals, electron spin, and magnetic field. However, single-phase polycrystalline manganese ore ceramic materials have a low intrinsic magnetoresistance (MR) effect. MR is the phenomenon where the resistance value changes with the applied magnetic field. The MR of a material is directly related to its practical application in magnetoresistance sensors and other fields. Therefore, the low intrinsic MR of single-phase polycrystalline manganese ore ceramic materials greatly limits the practical application of LCMO in related fields.
[0003] Currently, optimization strategies for the magnetoresistive performance of LCMO mainly focus on element doping and the construction of multiphase composite systems. For the construction of multiphase composite systems, although two-phase composite materials can improve the magnetoresistive performance of LCMO to a certain extent, the reinforcement effect of two-phase composite materials is relatively singular and lacks synergistic effect. Furthermore, the amount of the second phase other than LCMO added in two-phase composite materials is limited. Therefore, the optimization effect of two-phase composite materials on the magnetoresistive performance of LCMO materials is very limited.
[0004] Therefore, it is necessary to provide a Fe2O3, Ag2O and La 0.67 Ca 0.33 MnO3 three-phase co-composite ceramics and their preparation methods are used to improve the upper limit of the magnetoresistance effect enhancement of LCMO materials, thereby enabling the materials to have higher MR and expanding the application prospects of composite ceramics in related fields. Summary of the Invention
[0005] To overcome the problems existing in the background technology, the present invention obtains a three-phase composite ceramic by multi-phase compositing Fe2O3, Ag2O and LCMO ceramic materials. Under the combined effect of the grain boundary coating reinforcement of Fe2O3 and the excellent grain connectivity of Ag2O, the continuous flow of charge carriers is enhanced. Furthermore, after applying a magnetic field, the electron spins of the composite ceramic tend to be arranged in a regular and ordered manner. Thus, without negatively affecting the advantages of the LCMO ceramic material itself, the upper limit of the material's MR value is effectively improved, resulting in better MR of the three-phase composite ceramic, thereby further optimizing the practical application performance of the composite ceramic material.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention proposes a method using Fe2O3, Ag2O and La 0.67 Ca 0.33 MnO3 three-phase co-composite ceramic, wherein the chemical formula of the co-composite ceramic is La 0.67 Ca 0.33 MnO3 / x Fe2O3@ y Ag2O, where, x This refers to the molar content of Fe2O3 in the composite ceramic. x =0.1%, y This refers to the molar content of Ag₂O in the composite ceramic. y =5%-20%.
[0007] In another aspect, this invention provides a method for preparing the above-mentioned three-phase co-composite ceramic, the method comprising the following steps: (1) Weigh La according to the stoichiometric ratio 0.67 Ca 0.33 MnO3, Fe2O3, and Ag2O powders are mixed and ground, and then the ground powder mixture is pressed into a ceramic body.
[0008] (2) After sintering and annealing the ceramic blank obtained in step (1), La is obtained. 0.67 Ca 0.33 MnO3 / x Fe2O3@ y Ag2O three-phase co-composite ceramics.
[0009] Preferably, in step (1), the grinding time is 50 min.
[0010] Preferably, in step (1), the pressing pressure is 5~6MPa.
[0011] Preferably, in step (2), the sintering and annealing process is as follows: in an air atmosphere, the ceramic blank is heated to 600°C at a heating rate of 3°C / min, then heated to 1450°C at a heating rate of 4°C / min, held for 720 min, then cooled to 700°C at a cooling rate of 4°C / min, and finally cooled to room temperature with the furnace.
[0012] Preferably, the La 0.67 Ca 0.33 The preparation method of MnO3 powder includes the following steps: S1: Weigh manganese nitrate, calcium nitrate, and lanthanum nitrate according to the stoichiometric ratio. Add manganese nitrate, calcium nitrate, lanthanum nitrate, and the chelating agent to anhydrous methanol solvent, and stir the liquid until the nitrate particles are completely dissolved, obtaining a colorless, transparent, and uniformly mixed solution A. Since manganese nitrate is hygroscopic in air, in this step, weighing the manganese nitrate first and adding it to the anhydrous methanol solvent helps reduce the contact time between the manganese nitrate and air, thereby reducing the deliquescence rate and improving the weighing accuracy.
[0013] S2: Add a dispersant to solution A in step S1 to obtain mixed solution B. Heat and stir mixed solution B to obtain a waxy yellow wet gel that foams vigorously.
[0014] S3: The wet gel in step S2 is dried to obtain a loose and porous orange-yellow dry gel precursor, and then the dry gel precursor is ground into precursor powder.
[0015] S4: Calcine the precursor powder obtained in step S3 to obtain soot-like La. 0.67 Ca 0.33 MnO3 powder.
[0016] Preferably, in step S1, the chelating agent is anhydrous citric acid, and the molar ratio of the chelating agent, anhydrous methanol and the total amount of manganese nitrate, calcium nitrate and lanthanum nitrate (manganese nitrate, calcium nitrate and lanthanum nitrate are collectively referred to as nitrate raw materials) is total amount: chelating agent: anhydrous methanol = 1:4.67:(67.7824-75).
[0017] Preferably, in step S2, the heating temperature is 92°C, the reaction time is 20 min, the dispersant is ethylene glycol, and the molar ratio of the dispersant to the total amount of manganese nitrate, calcium nitrate, and lanthanum nitrate is total:dispersant = 1:1.5063. The dispersant content needs to be controlled within the aforementioned range; too much dispersant will inhibit foaming, while too little will lead to insufficient breaking of nitrate chemical bonds.
[0018] Preferably, in step S3, the drying temperature is 140°C, the drying time is not less than 8 hours, and the grinding time is 35 minutes.
[0019] Preferably, in step S4, the calcination process is as follows: in an air atmosphere, the precursor powder is heated to 200°C at a heating rate of 2°C / min and held for 30 min; then the precursor powder is heated to 400°C at a heating rate of 2°C / min and held for 30 min; then the precursor powder is heated to 500°C at a heating rate of 3°C / min and held for 480 min; finally, it is cooled to room temperature in the furnace.
[0020] The beneficial effects of this invention are: 1. This invention prepares a three-phase co-composite ceramic by multiphase composite formation of Fe2O3, Ag2O, and LCMO ceramic materials, combined with a specific preparation method, utilizing La... 0.67 Ca 0.33 At the interface between MnO3 and Fe2O3, Ag2O, there are diffusion and anti-diffusion effects, as well as grain boundary modification, which change the properties at the grain boundary and form new conductive and double exchange channels at the grain interface, thereby effectively improving the MR of the ceramic material. Compared with LCMO ceramics, the MR of the co-composite ceramic of this invention can be improved by 25%.
[0021] 2. The three-phase co-composite ceramic prepared by this invention has good crystallinity, high density, smooth surface, and excellent ceramic quality. Therefore, the composite of Fe2O3, Ag2O and LCMO in this invention will not have a negative impact on the performance of the ceramic material.
[0022] 3. The preparation method of this invention is simple, convenient, and low in cost, making it suitable for industrial application. Attached Figure Description
[0023] Figure 1 The XRD patterns are of the ceramics prepared in Examples 1-4 and Comparative Examples 1-2 of this invention.
[0024] Figure 2 This is a surface scan image of the LCMO polycrystalline ceramic prepared in Comparative Example 1 of this invention.
[0025] Figure 3 This is a cross-sectional scan of the three-phase co-composite ceramic prepared in Example 3 of the present invention.
[0026] Figure 4 This is an EDS scan of the three-phase co-composite ceramic prepared in Example 2 of the present invention.
[0027] Figure 5 The p-T curves of the LCMO polycrystalline ceramic prepared in Comparative Example 1 of this invention under magnetic fields of 0T and 1T are shown.
[0028] Figure 6 The p-T curves of the two-phase composite ceramic prepared in Comparative Example 2 of this invention under magnetic fields of 0T and 1T are shown.
[0029] Figure 7 The ρ-T curves of the three-phase co-composite ceramic prepared in Example 1 of the present invention under magnetic fields of 0T and 1T are shown.
[0030] Figure 8 The ρ-T curves of the three-phase co-composite ceramic prepared in Example 2 of the present invention under magnetic fields of 0T and 1T are shown.
[0031] Figure 9The ρ-T curves of the three-phase co-composite ceramic prepared in Example 3 of the present invention under magnetic fields of 0T and 1T are shown.
[0032] Figure 10 The ρ-T curves of the three-phase co-composite ceramic prepared in Example 4 of the present invention under magnetic fields of 0T and 1T are shown.
[0033] Figure 11 The images show the MR-T curves of the ceramics prepared in Comparative Examples 1-2 and Examples 1-4 of this invention. Detailed Implementation
[0034] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited to the content described.
[0035] Example 1 This embodiment prepares a three-phase co-composite ceramic using the following method. x =0.1%, y =5%.
[0036] (1) Accurately weigh manganese nitrate, calcium nitrate and lanthanum nitrate according to the stoichiometric ratio. Add manganese nitrate, calcium nitrate and lanthanum nitrate to a 250ml beaker containing anhydrous methanol solvent in sequence. At the same time, add anhydrous citric acid. The molar ratio of anhydrous citric acid, anhydrous methanol and nitrate raw materials is nitrate raw materials: anhydrous citric acid: anhydrous methanol = 1:4.67:67.7824. Place the beaker on a magnetic stirrer and stir thoroughly until the metal salt particles are completely dissolved to obtain a colorless, transparent and uniformly mixed solution A.
[0037] (2) Ethylene glycol was added dropwise to solution A as a dispersant to obtain mixed solution B. The molar ratio of ethylene glycol to nitrate raw material was nitrate raw material: ethylene glycol = 1:1.5063. Mixed solution B was placed on a 92℃ constant temperature heating stirrer and heated and stirred for 20 minutes to obtain a waxy yellow wet gel that foamed violently.
[0038] (3) Open the 140℃ constant temperature drying oven in advance, quickly put in the wet gel, and dry for 8 hours to obtain a loose and porous orange-yellow dry gel precursor.
[0039] (4) Wipe the agate mortar with alcohol and blow dry. Gently scrape the dry gel precursor into the mortar and grind for 35 minutes to obtain a fine-grained, waxy yellow precursor powder. Place the precursor powder in a muffle furnace and heat it to 200°C at a heating rate of 2°C / min and hold for 30 minutes. Then heat it to 400°C at a heating rate of 2°C / min and hold for 30 minutes. After that, heat it to 500°C at a heating rate of 3°C / min and hold for 480 minutes to volatilize excess inorganic matter. Finally, cool it to room temperature with the furnace to obtain a soot-like ceramic powder, namely La. 0.67 Ca 0.33 MnO3 powder.
[0040] (5) Weigh the La prepared in step (4) according to the stoichiometric ratio. 0.67 Ca 0.33 MnO3 powder, Fe2O3 powder, and Ag2O powder were mixed and ground for 50 minutes using a solid-state grinding method. The mixed powder was then pressed into a cylindrical ceramic blank using a tablet press at a pressure of 5 MPa.
[0041] (6) Place the ceramic green body in a muffle furnace and heat it to 600℃ at a heating rate of 3℃ / min, then heat it to 1450℃ at a heating rate of 4℃ / min, hold it at that temperature for 720 min, and then cool it to 700℃ at a cooling rate of 4℃ / min. Finally, allow the ceramic green body to cool to room temperature with the furnace. This eliminates residual stress. During this process, grains crystallize and grow, ultimately yielding La with good performance. 0.67 Ca 0.33 MnO3 / 0.001Fe2O3@0.05Ag2O three-phase co-composite polycrystalline ceramic.
[0042] Related experiments were conducted on the three-phase co-composite polycrystalline ceramic prepared in this embodiment, and the results are as follows: Figure 1 , 7 As shown in Figure 11.
[0043] pass Figure 1 As can be seen, the three-phase co-composite polycrystalline ceramic prepared in this embodiment exhibits a standard orthorhombic perovskite structure, with a relatively sharp strongest diffraction peak, indicating good crystallization quality.
[0044] pass Figure 7 It can be seen that the resistivity of the three-phase co-composite polycrystalline ceramic prepared in this embodiment is 0.024 Ω·cm under a 0T magnetic field and the metal-insulator transition temperature is 266K; the resistivity is 0.021 Ω·cm under a 1T magnetic field and the metal-insulator transition temperature is 276K.
[0045] pass Figure 11It can be seen that the magnetoresistance of the three-phase co-composite polycrystalline ceramic prepared in this embodiment is as high as 71%.
[0046] Combination Figure 7 as well as Figure 11 It can be seen that the three-phase co-composite polycrystalline ceramic prepared by this invention effectively improves the material's MR without compromising the inherent advantages of LCMO ceramic materials.
[0047] Example 2 This embodiment uses the same method as Example 1 to prepare three-phase co-composite ceramics, the difference being: In this embodiment... y =10%, the three-phase co-composite ceramic prepared in this embodiment is denoted as La. 0.67 Ca 0.33 MnO3 / 0.001Fe2O3@0.10Ag2O polycrystalline ceramic, the pressure for pressing the ceramic green body is 5.5MPa, nitrate raw materials: anhydrous citric acid: anhydrous methanol = 1:4.67:70.
[0048] Related experiments were conducted on the three-phase co-composite polycrystalline ceramic prepared in this embodiment, and the results are as follows: Figure 1 , 4 As shown in 8 and 11.
[0049] pass Figure 1 As can be seen, the three-phase co-composite polycrystalline ceramic prepared in this embodiment exhibits a standard orthorhombic perovskite structure, with a relatively sharp strongest diffraction peak, indicating good crystallization quality.
[0050] pass Figure 4 It can be seen that all elements in the three-phase co-composite polycrystalline ceramic prepared in this embodiment can be detected and are uniformly distributed.
[0051] pass Figure 8 It can be seen that the three-phase co-composite polycrystalline ceramic prepared in this embodiment has a resistivity of 0.023 Ω·cm and a metal-insulator transition temperature of 269 K under a 0 T magnetic field; and a resistivity of 0.020 Ω·cm and a metal-insulator transition temperature of 278 K under a 1 T magnetic field. This is quite similar to that of Example 1.
[0052] pass Figure 11 As can be seen, the magnetoresistance of the three-phase co-composite polycrystalline ceramic prepared in this embodiment is as high as 67%.
[0053] Example 3 This embodiment uses the same method as Example 1 to prepare three-phase co-composite ceramics, the difference being: In this embodiment... y =15%, the three-phase co-composite ceramic prepared in this embodiment is denoted as La. 0.67 Ca 0.33MnO3 / 0.001Fe2O3@0.15Ag2O polycrystalline ceramic, the pressure for pressing the ceramic green body is 6MPa, nitrate raw materials: anhydrous citric acid: anhydrous methanol = 1:4.67:75.
[0054] Related experiments were conducted on the three-phase co-composite polycrystalline ceramic prepared in this embodiment, and the results are as follows: Figure 1 , 3 As shown in 9 and 11.
[0055] pass Figure 1 As can be seen, the three-phase co-composite polycrystalline ceramic prepared in this embodiment exhibits a standard orthorhombic perovskite structure, with a relatively sharp strongest diffraction peak, indicating good crystallization quality.
[0056] pass Figure 3 As can be seen, the cross-section of the three-phase co-composite polycrystalline ceramic prepared in this embodiment shows that silver oxide is uniformly distributed in the LCMO crystal.
[0057] pass Figure 9 It can be seen that the La0.67Ca0.33MnO3 / xFe2O3@0.15Ag2O polycrystalline ceramic of this embodiment has a resistivity of 0.013Ω·cm and a metal-insulator transition temperature of 271K under a magnetic field of 0T; and a resistivity of 0.011Ω·cm and a metal-insulator transition temperature of 281K under a magnetic field of 1T.
[0058] Combination Figure 11 It can be seen that the magnetoresistance of the three-phase co-composite polycrystalline ceramic prepared in this embodiment is as high as 67%.
[0059] Example 4 This embodiment uses the same method as Example 1 to prepare three-phase co-composite ceramics, the difference being: In this embodiment... y =20%, the three-phase co-composite ceramic prepared in this embodiment is denoted as La. 0.67 Ca 0.33 MnO3 / 0.001Fe2O3@0.20Ag2O polycrystalline ceramic.
[0060] Related experiments were conducted on the three-phase co-composite polycrystalline ceramic prepared in this embodiment, and the results are as follows: Figure 1 , 10 As shown in Figure 11.
[0061] pass Figure 1 As can be seen, the three-phase co-composite polycrystalline ceramic prepared in this embodiment exhibits a standard orthorhombic perovskite structure, with a relatively sharp strongest diffraction peak, indicating good crystallization quality.
[0062] pass Figure 10It can be seen that the three-phase co-composite polycrystalline ceramic prepared in this embodiment has a resistivity of 0.010 Ω·cm and a metal-insulator transition temperature of 269 K under a 0 T magnetic field; and a resistivity of 0.008 Ω·cm and a metal-insulator transition temperature of 280 K under a 1 T magnetic field.
[0063] Combination Figure 11 It can be seen that the magnetoresistance of the three-phase co-composite polycrystalline ceramic prepared in this embodiment is as high as 69%.
[0064] Comparative Example 1 This comparative example uses the same method as Example 1 to prepare ceramic materials, the difference being that: this comparative example prepares single-phase La. 0.67 Ca 0.33 MnO3 ceramic material, without Fe2O3 and Ag2O composite.
[0065] Related experiments were conducted on the polycrystalline ceramics prepared in this comparative example, and the results are as follows: Figure 1 , 2 As shown in 5 and 11.
[0066] pass Figure 1 It can be seen that the single-phase polycrystalline ceramic prepared in this comparative example exhibits a standard orthorhombic perovskite structure, and the strongest diffraction peak is relatively sharp, indicating good crystallization quality.
[0067] pass Figure 2 It can be seen that the single-phase polycrystalline ceramic prepared in this comparative example has a smooth surface, good grain connectivity, and good grain crystallization quality.
[0068] pass Figure 5 It can be seen that the resistivity of the single-phase polycrystalline ceramic prepared in this comparative example is 0.022 Ω·cm under a magnetic field of 0T and the metal-insulator transition temperature is 266K; the resistivity is 0.019 Ω·cm under a magnetic field of 1T and the metal-insulator transition temperature is 277K.
[0069] pass Figure 11 It can be seen that the magnetoresistance of the single-phase polycrystalline ceramic prepared in this comparative example is 57%.
[0070] A comparison of Examples 1-4 with Comparative Example 1 shows that the other properties of the three-phase co-composite ceramics prepared in Examples 1-4 are relatively close to those of Comparative Example 1. However, the MR of the co-composite ceramic of Example 1 is 25% higher than that of Comparative Example 1, the MR of the co-composite ceramic of Example 2 is 18% higher than that of Comparative Example 1, the MR of the co-composite ceramic of Example 3 is 18% higher than that of Comparative Example 1, and the MR of the co-composite ceramic of Example 1 is 21% higher than that of Comparative Example 1. This indicates that the three-phase co-composite ceramics prepared by the present invention can effectively improve the MR without negatively affecting other properties of the ceramic.
[0071] In the three-phase co-composite ceramic prepared by this invention, Fe2O3 is a high-resistivity oxide. The composite Fe2O3 and Ag2O adhere to and coat the grain and grain boundary surfaces in the form of free particles in the LCMO system, increasing the volume fraction and disorder of the grain boundaries and enhancing the scattering effect of the grain boundaries on the charge carriers. After applying a magnetic field, the electron spin tends to be arranged in a regular and ordered manner, making the decrease in resistance more obvious, thereby effectively improving the MR of the three-phase co-composite ceramic.
[0072] Comparative Example 2 This comparative example uses the same method as Example 1 to prepare ceramic materials, the difference being that: this comparative example prepares a two-phase composite La... 0.67 Ca 0.33 MnO3 / 0.001Fe2O3 ceramic material, without Ag2O composite.
[0073] Related experiments were conducted on the two-phase composite ceramic prepared in this comparative example, and the results are as follows: Figure 1 , 6 As shown in Figure 11.
[0074] pass Figure 1 It can be seen that the two-phase composite polycrystalline ceramic prepared in this comparative example exhibits a standard orthorhombic perovskite structure, and the strongest diffraction peak is relatively sharp, indicating good crystallization quality.
[0075] pass Figure 6 It can be seen that the resistivity of the two-phase composite polycrystalline ceramic prepared in this comparative example is 0.028 Ω·cm under a magnetic field of 0T and the metal-insulator transition temperature is 262K; the resistivity is 0.023 Ω·cm under a magnetic field of 1T and the metal-insulator transition temperature is 272K.
[0076] pass Figure 11 It can be seen that the magnetoresistance of the two-phase composite polycrystalline ceramic prepared in this comparative example is 59%.
[0077] Comparing Comparative Example 1 and Comparative Example 2, it can be seen that when LCMO and Fe2O3 are combined in a two-phase manner, the MR of the ceramic material can be improved to a certain extent. However, the improvement effect is very limited, only 2%. Therefore, the improvement effect of two-phase combination on the MR of ceramic materials is greatly limited. The strengthening ability of a single second phase is limited, and the amount of second phase added is also limited. For example, Fe2O3 has high resistivity characteristics, and too much Fe2O3 can easily lead to excessive insulation of grain boundaries, reducing carrier mobility; while too much Ag2O may cause phase separation, affecting the compactness of the material.
[0078] In summary, this invention prepares a high-quality, high-MR three-phase co-composite ceramic by multiphase composite of Fe2O3, Ag2O and LCMO ceramic materials and a combined preparation method. Without negatively impacting other advantageous properties of LCMO ceramic materials, it effectively improves MR and raises the upper limit of MR, resulting in a better MR for the three-phase co-composite ceramic, thereby further optimizing the practical application performance of the composite ceramic material.
[0079] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.
Claims
1. A mixture of Fe2O3, Ag2O, and La 0.67 Ca 0.33 MnO3 three-phase co-composite ceramic, characterized in that: The chemical formula for the co-composite ceramic is La. 0.67 Ca 0.33 MnO3 / x Fe2O3@ y Ag2O, where, x This refers to the molar content of Fe2O3 in the composite ceramic. x =0.1%, y This refers to the molar content of Ag₂O in the composite ceramic. y =5%-20%.
2. The Fe2O3, Ag2O and La compound according to claim 1 0.67 Ca 0.33 The method for preparing MnO3 three-phase co-composite ceramics is characterized by: The preparation method includes the following steps: (1) Weigh La according to the stoichiometric ratio 0.67 Ca 0.33 MnO3, Fe2O3, and Ag2O powders are mixed and ground, and then the ground powder mixture is pressed into a ceramic body. (2) After sintering and annealing the ceramic blank obtained in step (1), La is obtained. 0.67 Ca 0.33 MnO3 / x Fe2O3@ y Ag2O three-phase co-composite ceramics.
3. The preparation method according to claim 2, characterized in that: In step (1), the grinding time is 50 minutes.
4. The preparation method according to claim 2, characterized in that: In step (1), the pressing pressure is 5~6MPa.
5. The preparation method according to claim 2, characterized in that: In step (2), the sintering and annealing process is as follows: In an air atmosphere, the ceramic blank is heated to 600°C at a heating rate of 3°C / min, then heated to 1450°C at a heating rate of 4°C / min, held for 720 min, then cooled to 700°C at a cooling rate of 4°C / min, and finally cooled to room temperature with the furnace.
6. The preparation method according to claim 2, characterized in that: The La 0.67 Ca 0.33 The preparation method of MnO3 powder includes the following steps: S1: Weigh manganese nitrate, calcium nitrate, and lanthanum nitrate according to the stoichiometric ratio. Add manganese nitrate, calcium nitrate, lanthanum nitrate, and chelating agent to anhydrous methanol solvent and stir the liquid until the nitrate particles are completely dissolved to obtain a colorless, transparent, and uniformly mixed solution A. S2: Add a dispersant to solution A in step S1 to obtain mixed solution B. Heat and stir mixed solution B to obtain a waxy yellow wet gel that foams violently. S3: The wet gel in step S2 is dried to obtain a loose and porous orange-yellow dry gel precursor, and then the dry gel precursor is ground into precursor powder. S4: Calcine the precursor powder obtained in step S3 to obtain soot-like La. 0.67 Ca 0.33 MnO3 powder.
7. The preparation method according to claim 6, characterized in that: In step S1, the chelating agent is anhydrous citric acid, and the molar ratio of the total amount of chelating agent, anhydrous methanol, manganese nitrate, calcium nitrate, and lanthanum nitrate is: total amount: chelating agent: anhydrous methanol = 1:4.67:(67.7824-75).
8. The preparation method according to claim 6, characterized in that: In step S2, the heating temperature is 92℃, the reaction time is 20min, the dispersant is ethylene glycol, and the molar ratio of the amount of dispersant added to the total amount of manganese nitrate, calcium nitrate, and lanthanum nitrate is total:dispersant = 1:1.5063.
9. The preparation method according to claim 6, characterized in that: In step S3, the drying temperature is 140℃, the drying time is not less than 8 hours, and the grinding time is 35 minutes.
10. The preparation method according to claim 6, characterized in that: In step S4, the specific calcination process is as follows: In an air atmosphere, the precursor powder is heated to 200°C at a heating rate of 2°C / min and held for 30 min; then the precursor powder is heated to 400°C at a heating rate of 2°C / min and held for 30 min; then the precursor powder is heated to 500°C at a heating rate of 3°C / min and held for 480 min; finally, it is cooled to room temperature in the furnace.
Citation Information
Patent Citations
Method for preparing silver-doped lanthanum calcium manganese oxygen polycrystalline ceramic target
CN110451961A
